Analisis Karakteristik Perusahaan Yang Mempengaruhi Nilai Perusahaan Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2010-2014 - Budi Wahyu Mahardhika; Anita Roosmawarni (UMSurabaya Publishing, 2016)
The purpose of this study is to analyze the impact of the variables: leverage (DAR), firm size (SIZE), market growth (GROWTH), profitability (ROE), firm age (AGE), managerial ownership (KM), Deviden policy (DPR) and liquidity (CR) on firm value (PBV) on manufacturing companies listed in Indonesia Stock Exchange 2010-2014 period. Research using purposive sampling method for taking samples. Data obtained on the basis of the publication of Indonesian Capital Market Directory (ICMD), obtained 29 samples of manufacturing firms.The analysis technique used is multiple regression analysis. The F statistic test shows the model meets the criteria of fit because it has a significance value of less than 5% significance level. The result of t-test indicates that firm size and profitability significantly affect to the value of the firm because of it has a significance value of less than 5% significance level. While variable leverage, growth, age, liquidity, deviden policy and managerial ownership do not affect the value of the firm because they have a significance value of more than 5%.The result shows that predictive ability of the eight independent variables (leverage, firm size, growth, profitability, age, managerial ownership, deviden policy and liquidity) is 14,9%. Key Words: Characteristics Of The Firm, Leverage (DAR), Firm size (SIZE), Market Growth (GROWTH), Profitability (ROE), Firm Age (AGE), Managerial Ownwership (KM), Liquidity (CR), Deviden Policy (DPR), Price book value (PBV) and Manufacturing Companies